2017
DOI: 10.1159/000455819
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Thompson Encephalopathy Score and Amplitude-Integrated Electroencephalography in Infants with Perinatal Asphyxia and Therapeutic Hypothermia

Abstract: Background: In previous studies clinical signs or amplitude-integrated electroencephalography (aEEG)-based signs of encephalopathy were used to select infants with perinatal asphyxia for treatment with hypothermia. Aim: The objective of this study was to compare Thompson encephalopathy scores and aEEG, and relate both to outcome. Subjects and Methods: Thompson scores, aEEG, and outcome were compared in 122 infants with perinatal asphyxia and therapeutic hypothermia. Of these 122 infants, 41 died and 7 had an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…On the other hand, mild therapeutic hypothermia would decrease the activity of brain. When therapeutic hypothermia is used, the predictive value of the aEEG is delayed until 24-36 h [5]. Therefore, when sedatives and anesthetics were used for patients during therapeutic hypothermia after cardiac arrest, the value of BIS was not consistent with the activity of brain.…”
mentioning
confidence: 99%
“…On the other hand, mild therapeutic hypothermia would decrease the activity of brain. When therapeutic hypothermia is used, the predictive value of the aEEG is delayed until 24-36 h [5]. Therefore, when sedatives and anesthetics were used for patients during therapeutic hypothermia after cardiac arrest, the value of BIS was not consistent with the activity of brain.…”
mentioning
confidence: 99%
“…In accordance with the large trials, TH should be reserved for neonates ≥36 weeks and ≤6 hours old with evidence of possible intrapartum hypoxia-ischaemia (Apgar score ≤5 at 10 minutes, or continued resuscitation at 10 minutes, or severe acidosis (pH <7/base deficit (BD) ≥16) and an abnormal neurological examination (moderate/severe encephalopathy or clinical seizures or an abnormal aEEG). Although the use of the Thompson score to determine eligibility cannot be disregarded, there is no consensus on the ideal numerical threshold that should be used as Horn et al [30] suggest ≥7, Weeke et al [27] suggest ≥11 and Thorsen et al [28] suggest ≥12, and therefore further large studies are necessary. Institutions using the Thompson score to determine eligibility should select a threshold according to the resources available at that facility, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…This study also showed that there was no significant difference in the ability of either an early Thompson score or the modified Sarnat stages to predict an abnormal aEEG by 6 hours of age. [30] Weeke et al [27] showed a significant association between the Thompson score and abnormal aEEG patterns. The scores of neonates with discontinuous normal voltage (DNV) and burst suppression (BS) were significantly different (>7 v. ≥10), as were the scores of neonates with BS and continuous low voltage (CLV)/flat trace (FT) (≥10 v. ≥12/15).…”
Section: Supportive Carementioning
confidence: 98%
See 2 more Smart Citations